ENHANCE MANAGEMENT CORRELATION OF LABORATORY CBR VALUE AND DCP IN LANDCOMPENSATED ON ROAD CONSTRUCTION HIGH CLAB TOLL – INDERAPURA - Jupriah Sarifah; Bangun Pasaribu (SEAN Institute, 2023)
How to test the Dynamic Cone Penetrometer (DCP). It is a quick procedure for evaluating the strength of subgrade and road base layers at a relatively low cost. This paper discusses the relationship between laboratory CBR and DCP values ​​for compacted soil on the inderapura high cliff toll road. The CBR test is a test that is well known in general, especially in the construction of toll roads and landfills. However, this CBR test has some drawbacks. For this reason, the DCP test is used as a substitute for the CBR test. This research, which has been conducted, produces a graph of the correlation between CBR and DCP values ​​with different calculations. In this study, we will look for correlation calculations of CBR and DCP values ​​in soils that are close to the actual CBR values. The data is obtained by compacting the soil, laboratory CBR test and continued with DCP which all activities are in the field and in the laboratory. CBR values ​​using the DCP test were 4.73, 10.31, 3.68 while laboratory CBR values ​​were obtained from samples of 8.02%, 7.29%, 5.20%. From the analysis carried out, the CBR and DCP values ​​are not much different from the laboratory CBR values.